Notre-Dame de Paris: The first iron lady? Archaeometallurgical study and dating of the Parisian cathedral iron reinforcements - L’Héritier, Maxime (2023)
The study of iron reinforcements used in the construction of Notre-Dame de Paris offers a glimpse into the innovation that took place on this building site in the mid-12th century, adapting metal to create a novel architecture. The restoration of the monument after the 2019 fire offered unique possibilities to investigate its iron armatures and to sample 12 iron staples from different locations (tribunes, nave aisles and upper walls). Six of them were dated thanks to the development of an innovative methodology based on radiocarbon dating. They reveal that Notre-Dame is the first known Gothic cathedral where iron was massively used as a proper construction material to bind stones throughout its entire construction, leading to a better understanding of the master masons’ thinking. Moreover, a metallographic study and slag inclusion chemical analyses of the staples provide the first study of iron supply for a great medieval Parisian building yard, renewing our understanding of iron circulation, trade and forging in the 12th and 13th century capital of the French kingdom. The highlighting of numerous welds in all iron staples and the multiple provenances sheds light on the activity of the iron market in this major medieval European city and the nature of the goods that circulated, and questions the possible importance of recycling.